Solve for y 8-2(3-4y)=7y-1

Math
8-2(3-4y)=7y-1
Simplify 8-2(3-4y).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
8-2⋅3-2(-4y)=7y-1
Multiply -2 by 3.
8-6-2(-4y)=7y-1
Multiply -4 by -2.
8-6+8y=7y-1
8-6+8y=7y-1
Subtract 6 from 8.
2+8y=7y-1
2+8y=7y-1
Move all terms containing y to the left side of the equation.
Tap for more steps…
Subtract 7y from both sides of the equation.
2+8y-7y=-1
Subtract 7y from 8y.
2+y=-1
2+y=-1
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 2 from both sides of the equation.
y=-1-2
Subtract 2 from -1.
y=-3
y=-3
Solve for y 8-2(3-4y)=7y-1

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top